Driven to Stay or Prone to Leave? Exploring Distributor Retention in MLM Through Herzberg’s Lens - Oktanita Jaya Anggraeni; Alwan Abdurahman; Amalia Dwi Marseva; Jemi Cahya Adi Wijaya (Indonesian Journal Publisher, 2025)
Multi-Level Marketing (MLM) companies depend heavily on the loyalty and continuity of their distributor networks. However, distributor retention remains a significant challenge due to factors such as dissatisfaction with compensation and lack of recognition. This study investigates the influence of motivator and hygiene factors on distributor retention using Herzberg's Two-Factor Theory. Employing a quantitative correlational design, data were collected from 200 active MLM distributors across Indonesia through a structured questionnaire. The results reveal that both motivator and hygiene factors significantly influence distributor retention, with motivators showing a stronger impact. These findings underscore the importance of intrinsic job satisfaction elements in designing effective distributor retention strategies. The study extends the application of Herzberg’s theory to the MLM industry, emphasizing its relevance in informal and network-based business settings.